Fabry's disease and stroke: Effectiveness of enzyme replacement therapy (ERT) in stroke prevention, a review with meta-analysis. (July 2019) - Sheng, Sen; Wu, Leihong; Nalleballe, Krishna; Sharma, Rohan; Brown, Aliza; Ranabothu, Saritha; Kapoor, Nidhi; Onteddu, Sanjeeva
Highlights: Fabry disease is most prevalent lysosomal storage disorder with multi-organ involvement including ischemic stroke. Our meta-analysis on the currently available data showed that enzyme replacement treatment for Fabry's disease has beneficial effect on stroke prevention. Indications for enzyme replacement therapy might need to be broadened to female carriers and atypically affected males. Abstract: Back ground and objective: Fabry's disease, is the most prevalent lysosomal storage disorder and is notorious for its early multi-organ involvement leading to complications, including ischemic strokes and transient ischemic attacks. Since 2001, enzyme replacement therapy (ERT) has become the mainstay treatment for Fabry's patients but the indications are not clearly defined. We did a meta-analysis of the available data to review the benefit of ERT for stroke prevention in Fabry's patients. Methods: A literature search was performed from National Center for Biotechnology information (NCBI)/PubMed database without restriction of years for systematic review purposes. A systematic review of clinical cohort studies and trials was performed with pooled analysis of proportions. The pooled proportions and the confidence intervals (CI) for stroke recurrence ratio were calculated for both ERT treatment group and native treatment groups. Result: A total of 7 cohort studies and 2 RCTs involving 7513 participants (1471 on ERT vs 6042 on native treatment) met inclusion criteria. The pooled proportions analysis showed that the stroke recurrence ratio in the ERT treatment group was 8.2% [95% CI 0.038, 0.126] and in native-treatment group was 16% [95% CI; 0.102, 0.217]. Effect differences favored ERT treatment group over native treatment group (p = 0.03). Conclusion: Our meta-analysis based on the currently available data showed that ERT for Fabry's disease has beneficial effect on stroke prevention. Female carriers and atypically affected males could be started on ERT as soon as diagnosis is made. Further studies are warranted to support the role of ERT in stroke prevention.